Rancang Bangun Sistem Pengaman Kotak Dana Punia berbasis Mikrokontroler NodeMCU ESP32 dan Aplikasi Telegram - Suriana , I Wayan; Setiawan , I Gede Adi; Graha, I Made Satya (Jurnal Ilmiah Telsinas, 2021)
The Dana Punia box security system is a security that can be monitored with online chat media in order to minimize crimes that occur in temples. This tool will work after connecting to the internet via ESP32 which can detect nearby Wifi networks. The hardware consists of the NodeMCU ESP32 board as the main controller, the telegram application as a message/notification receiver, a magnetic sensor as a notification if there is an act of theft and a fingerprint as access to open the money box. Based on the results, it can be concluded that this tool can work according to the designed working principle. This is indicated by the operation of the telegram application as a recipient of messages notifications, and a magnetic sensor as a notification if there is an act of theft and a fingerprint which is a tool to open the money box. Keyword : Telegram application, NodeMCU ESP32, fingerprint, magnetic sensor.